The influence of perceived product risk on consumer trust in Pertamina's fuel products: The moderating role of media exposure - Arihta Tarigan; Carmel Karaniya Wigayha; Agung Stefanus Kembau; Ruth Nattassha; I Gede Wisnu Satria Chandra Putra (Universitas Nusa Cendana, 2026)
This study investigates the effect of perceived product risk on consumer trust in Pertamina's fuel products, with media exposure serving as a moderating variable. Conducted in the context of the 2025 corruption scandal and concerns over fuel quality discrepancies, the study adopts a quantitative approach using data collected from 103 urban consumers in the Greater Jakarta (Jabodetabek) area. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings demonstrate that perceived product risk exerts a significant negative effect on consumer trust, indicating that concerns regarding product quality and reliability substantially undermine public confidence. Media exposure significantly moderates this relationship, amplifying the influence of perceived risk on trust. The model explains a substantial proportion of the variance in consumer trust, highlighting the critical role of public information during periods of institutional crisis. These findings underscore the importance of integrating rigorous quality assurance with transparent and proactive communication strategies to restore consumer confidence. The study contributes to the literature on crisis management, consumer trust, and state-owned enterprises by demonstrating how media exposure shapes public responses to perceived product risk during organizational recovery. Keywords: Consumer Trust; Media Exposure; Perceived Risk; Petroleum Industry; Trust Recovery